Carceral atmospheres on Manus Island: Listening to how are you today - Emma K Russell (Law Text Culture, 2020)
This paper develops a conception of ‘carceral atmospheres’ as a way of framing our encounter with the sound art and archive how are you today, created by the Manus Recording Project Collective (MRPC). This 2018 work involved the creation and collection of 84 field recordings by six asylum seekers and refugees indefinitely detained on Manus Island by the Australian government. I argue that a proper engagement with the medium and mode of production of how are you today – that is, offshore detention and transborder solidarity – requires a sensory politics that is attuned to the dynamic and increasingly diffuse nature of carceral power. The paper explores the tension between the tangible and intangible nature of carceral space, the heterogeneity of prison soundscapes and the significance of time to experiences of punishment. Complicating the presumption of sound as object of analysis, I consider how field recordings both convey and create atmospheres.